Resveratrol acts via the mitogen-activated protein kinase (MAPK) pathway to protect retinal ganglion cells from apoptosis induced by hydrogen peroxide. Issue 1 (1st January 2021) - Ye, Ming-jing; Meng, Ni
ABSTRACT: The current study investigated the ability of resveratrol to protect RGC-5 retinal ganglion cells in culture against H2 O2 -induced apoptosis and the underlying mechanism of protection. RGC-5 cells were pre-exposed to resveratrol (5, 10, or 20 μM), followed by 200 μM H2 O2 . Cell viability and apoptosis were detected to assess the cell growth, and expression levels of apoptosis-related and MAPK cascade-associated proteins were determined using western blotting. Levels of reactive oxygen species and mitochondrial membrane potential were also tested, as well as the activities of superoxide dismutase (SOD), catalase (CAT), and glutathione S-transferase (GSH). At a concentration-dependent way, resveratrol reversed H2 O2 -induced increases in expressions of cleaved caspase-3 and cleaved caspase-9, production of ROS, loss of mitochondrial membrane potential and the expressions of p-p38, p-ERK, and p-JNK. It also promoted the activities of SOD, CAT, and GSH. Furthermore, the agonists of p38, ERK, and JNK partially weakened the protective effects of resveratrol against H2 O2 -induced apoptosis in RGC-5 cells. Thus, resveratrol can protect retinal ganglion cells against H2 O2 -induced apoptosis by suppressing MAPK cascades. The drug therefore shows potential for preventing glaucoma. Graphical abstract: uf0001